Flying High in Academia—Willingness of University Staff to Perform Low-Carbon Behavior Change in Business Travel - Thaller, Annina; Schreuer, Anna; Posch, Alfred (Frontiers in Sustainability, 2021)
This study aims to explore the factors that influence business travel decisions of university staff, in particular the extent and ways in which they are willing to reduce emission-intensive air travel, and the personal and structural barriers to such behavior change. Three strategies to reduce air travel were investigated: abstaining from particular events, substituting travel through virtual participation and mode shifting to ground-based public transport. We tested the effects of (1) specific decision factors for engaging in long-distance travel, choosing specific modes of travel and choosing virtual solutions; (2) former travel activities; (3) postponed trips due to COVID-19; and (4) sociodemographic factors, on the willingness of individuals to reduce air travel in a sample of university employees. We calculated regression models for the three strategies and added a qualitative analysis of open-ended comments. Former travel behavior as well as pro-environmental considerations play significant roles, influencing the willingness of employees to change their business travel behavior. Furthermore, we found that willingness to reduce air travel depends on the scope of behavior change. Although travel behavior is unevenly distributed across different subgroups, sociodemographic factors only play a minor role in the regression models. The present study adds to the limited body of quantitative research on the reduction potential of academic air travel, presenting an examination of university staff's willingness to change their long-distance travel behavior. Implications for university polices are discussed.